Orchestrating the Circular Smart Palm Ecosystem: A Design Science Research Using TOGAF-Based Enterprise Architecture - Hamdani, Ibnu; Indrajit, Richardus Eko; Firizqi, Januponsa Dio (Sinkron : jurnal dan penelitian teknik informatika, 2026)
The global palm oil industry is currently confronting a sustainability trilemma involving production efficiency, regulatory compliance (e.g., EUDR), and environmental circularity. Existing supply chain models are characterized by fragmented information systems, where Operational Technology (OT) remains disconnected from Enterprise IT, resulting in traceability gaps and underutilized biomass waste. This study addresses these challenges by designing a comprehensive Enterprise Architecture (EA) for a Circular Smart Palm ecosystem. Adopting a Design Science Research (DSR) methodology, the research applies the TOGAF Architecture Development Method (ADM), supported by ArchiMate 3.1 modeling, to develop an integrated architectural blueprint. The proposed architecture consolidates blockchain-enabled traceability, digital export compliance, IoT-driven bioenergy valorization, and value-added kernel processing into a unified enterprise framework. The resulting architecture is qualitatively validated through architectural consistency analysis and gap assessment between the As-Is and To-Be states. From a theoretical perspective, this study contributes to Enterprise Architecture literature by extending EA as an integrative mechanism for circular bioeconomy implementation in sustainability-driven agribusiness ecosystems. The findings demonstrate that enterprise-level architectural integration can transform sustainability compliance from an operational constraint into a strategic enabler for traceability, circular value creation, and digital governance.